Characterization of Swallowing Sound: Preliminary Investigation of Normal Subjects - Honda, Tsuyoshi; Baba, Takuro; Fujimoto, Keiko; Goto, Takaharu; Nagao, Kan; Harada, Masafumi; Honda, Eiichi; Ichikawa, Tetsuo (PloS one, 2016)
The purpose of this study was to characterize the swallowing sound and identify the process of sound generation during swallowing in young healthy adults. Thirty-three healthy volunteers were enrolled and allocated into three experimental groups. In experiment 1, a microphone was attached to one of eight cervical sites in 20 subjects, participants swallowed 5 ml water, and the sound waveform was recorded. In experiment 2, 10 subjects swallowed either 0, 5, 10, or 15 ml water during audio recording. In addition, participants consumed the 5 ml bolus in two different cervical postures. In experiment 3, the sound waveform and videofluoroscopy were simultaneously recorded while the three participants consumed 5 ml iopamidol solution. The duration and peak intensity ratio of the waveform were analyzed in all experimental groups. The acoustic analysis of the waveforms and videofluoroscopy suggested that the swallowing sound could be divided into three periods, each associated with a stage of the swallowing movement: the oral phase comprising posterior tongue and hyoid bone movement; the pharyngeal phase comprising larynx movement, hyoid bone elevation, epiglottis closure, and passage of the bolus through the esophagus orifice; and the repositioning phase comprising the return of the hyoid bone and larynx to their resting positions, and reopening of the epiglottis. Acoustic analysis of swallowing sounds and videofluoroscopy suggests that the swallowing sound could be divided into three periods associated with each process of the swallowing movement: the oral phase comprising the posterior movement of the tongue and hyoid bone; the pharyngeal phase comprising the laryngeal movement, hyoid bone elevation, epiglottis closure, and the bolus passage to the esophagus orifice; and the repositioning phase comprising the repositioning of the hyoid bone and larynx, and reopening of the epiglottis.